Movements of a deep-water fish: establishing marine fisheries management boundaries in coastal Arctic waters - Hussey, Nigel E; Hedges, Kevin J; Barkley, Amanda N; Treble, Margaret A; Peklova, Iva; Webber, Dale M; Ferguson, Steven H; Yurkowski, David J; Kessel, Steven T; Bedard, Jeannette M; Fisk, Aaron T (Ecological applications, 2017)
Management boundaries that define populations or stocks of fish form the basis of fisheries planning. In the Arctic, decreasing sea ice extent is driving increasing fisheries development, highlighting the need for ecological data to inform management. In Cumberland Sound, southwest Baffin Island, an indigenous community fishery was established in 1987 targeting Greenland halibut (Reinhardtius hippoglossoides) through the ice. Following its development, the Cumberland Sound Management Boundary (CSMB) was designated and a total allowable catch (TAC) assigned to the fishery. The CSMB was based on a sink population of Greenland halibut resident in the northern section of the Sound. Recent fishing activities south of the CSMB, however, raised concerns over fish residency, the effectiveness of the CSMB and the sustainability of the community-based winter fishery. Through acoustic telemetry monitoring at depths between 400 and 1200 m, and environmental and fisheries data, this study examined the movement patterns of Greenland halibut relative to the CSMB, the biotic and abiotic factors driving fish movement and the dynamics of the winter fishery. Greenland halibut undertook clear seasonal movements between the southern and northern regions of the Sound driven by temperature, dissolved oxygen, and sea ice cover with most fish crossing the CSMB on an annual basis. Over the lifespan of the fishery, landfast ice cover initially declined and then became variable, limiting accessibility to favored fisher locations. Concomitantly, catch per unit effort declined, reflecting the effect of changing ice conditions on the location and effort of the fishery. Ultimately, these telemetry data revealed that fishers now target less productive sites outside of their favored areas and, with continued decreases in ice, the winter fishery might cease to exist. In addition, these novel telemetry data revealed that the CSMB is ineffective and led to its relocation to the entrance of the Sound in 2014. The community fishery can now develop an open-water fishery in addition to the winter fishery to exploit the TAC, which will ensure the longevity of the fishery under projected climate-change scenarios. Telemetry shows great promise as a tool for understanding deep-water species and for directly informing fisheries management of these ecosystems that are inherently complex to study.
Keywords: Arktida; zachování přírodních zdrojů; Animals; Arctic Regions; Flounder; rybářství; Animal Migration; Conservation of Natural Resources; Kanada; Oceans and Seas; platýs; Animal Distribution; oceány a moře; Fisheries; technologie dálkového snímání; Canada; migrace zvířat; Remote Sensing Technology; zvířata; rozšíření zvířat